A nanoparticle-modified aerogel material and a preparation method thereof
By using specific combinations of modified gel agents in nano-aerogel materials and impregnation treatment of nano-aerogel materials, the coordinated improvement of wear resistance and thermal insulation and high-temperature acid and corrosion stability are solved. The problem of this achieves more efficient performance improvement.
Patent Information
- Application Number
- CN202310860302.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-07-13
AI Technical Summary
The existing nano aerogel materials are difficult to coordinately improve their wear resistance and thermal insulation, and have poor performance stability under acid corrosion and high temperature conditions, which limits the efficiency of the product.
Silica aerogel is used as the matrix, and modified by modifying the phenolic resin adhesive, whisker-adjusted glass microbead dual-effect agent, chitosan aqueous solution, silane coupling agent KH560 and sheet alumina The nanoparticle modified aerogel material is formed by co-forming agents and impregnation treatment is carried out in the nanoparticle modified solution.
It significantly improves the insulation and wear resistance of the product, and maintains stability under acid corrosion and high temperature conditions, enhancing the efficiency of the product.
Smart Images

Figure BDA0004337492600000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel materials, and in particular to a nanoparticle-modified aerogel material and a preparation method thereof. Background Art
[0002] Aerogel refers to a nano-scale porous solid material formed by using a sol-gel method to replace the liquid phase in the gel with gas in a certain drying method, such as gelatin, gum arabic, silica gel, hair, nails, etc. Aerogel also has the properties of gel, that is, it has expansion, thixotropy, and slurry separation.
[0003] It is difficult to achieve coordinated improvements in the wear resistance and thermal insulation of existing nano-aerogel materials, which affects the efficiency of product use. At the same time, the performance stability of nano-aerogel deteriorates under acid corrosion and heat resistance conditions, further limiting the efficiency of product use. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a nanoparticle-modified aerogel material and a preparation method thereof to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a nanoparticle modified aerogel material, wherein the aerogel material uses a gel core layer made of silica aerogel as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, and finally is immersed in a nanoparticle modified liquid to obtain a nanoparticle modified aerogel material;
[0007] The modified adhesive comprises the following raw materials in parts by weight:
[0008] 35-40 parts of phenolic resin adhesive, 16-22 parts of whisker regulating glass microbead dual-effect agent, 4-8 parts of chitosan aqueous solution, 3-6 parts of silane coupling agent KH560, 2-5 parts of flaky aluminum oxide modifier, and 30-40 parts of ethanol.
[0009] The inventors of the present invention found that the performance of the product deteriorated significantly when the whisker regulating glass microbead dual-effect agent was not added, the flaky alumina modifier was not added, and the nanoparticle modification liquid impregnation treatment was not used. The performance effect of the product was most obvious when the three were mixed and synergistically enhanced.
[0010] Preferably, the mass fraction of the chitosan aqueous solution is 4-9%.
[0011] Preferably, the preparation method of the whisker regulating glass microbead dual-effect agent is:
[0012] S01: adding silicon carbide whiskers to yttrium nitrate solution at a weight ratio of 1:6, then adding sodium dodecyl sulfate solution with a weight of 5-10% of the total amount of silicon carbide whiskers and sodium silicate aqueous solution with a weight of 3-5% of the total amount of silicon carbide whiskers, stirring evenly to obtain a silicon carbide whisker conditioning solution;
[0013] S02: adding hydrochloric acid accounting for 5-10% of the total amount of the sodium alginate aqueous solution and silica sol accounting for 1-5% of the total amount of the sodium alginate aqueous solution to a sodium alginate aqueous solution having a mass fraction of 10-15%, stirring evenly to obtain a pre-modified solution;
[0014] S03: The glass microspheres are first treated at 100-110°C for 10-20 minutes, then cooled to 40-45°C at a rate of 1-3°C / min, kept warm, and then 10-15% of the total amount of the warmed product is added with a pre-modified liquid, ball milled for 1-2 hours at a ball milling speed of 1000-1500r / min, and after the ball milling is completed, washed with water and dried to obtain pre-adjusted glass microspheres;
[0015] S04: Adding the regulating glass microbeads into the silicon carbide whisker regulating liquid at a weight ratio of 1:5 for stirring and reaction treatment, and after the stirring is completed, washing and drying are performed to obtain the whisker regulating glass microbead dual-effect agent.
[0016] Silicon carbide whiskers are distributed in the system as whisker matrix. The dispersion and stability of the whiskers are improved by optimizing and blending sodium dodecyl sulfate solution and sodium silicate aqueous solution. The pre-adjusted glass microbeads are heat-treated and then ball-milled with pre-modified liquid. The pre-adjusted glass microbeads can be stirred and reacted with the silicon carbide whisker conditioning liquid, and the synergistic effect is enhanced, which can provide significant improvements in the thermal insulation and wear resistance of the product.
[0017] The inventors of the present invention have found that the pre-adjusted glass microbeads are replaced by glass microbeads in the preparation of the whisker-adjusting glass microbead dual-effect agent in the modified adhesive, the pre-modified liquid is not used in the preparation of the whisker-adjusting glass microbead dual-effect agent in the modified adhesive, and the ball milling treatment is directly performed, and the silicon carbide whisker regulating liquid is not added to the silicon carbide whisker regulating liquid in the preparation of the whisker-adjusting glass microbead dual-effect agent in the modified adhesive, and the organic alcohol amine is not used in the preparation of the flaky aluminum oxide modifier, and the ball milling treatment is directly performed. The performance of the products has a tendency to deteriorate. Only the whisker-adjusting glass microbead dual-effect agent prepared by the method of the present invention has the most significant performance effect.
[0018] Preferably, the mass fraction of the yttrium nitrate solution is 3-6%; the mass fraction of the sodium silicate aqueous solution is 10-15%.
[0019] Preferably, the sodium dodecyl sulfate solution is prepared by mixing a 6% by mass sodium dodecyl sulfate aqueous solution and a 2% by mass lanthanum chloride solution in a weight ratio of 3:1.
[0020] Preferably, the rotation speed of the S04 stirring reaction treatment is 550-750 r / min, the stirring time is 20-30 min, and the stirring temperature is 45-48°C.
[0021] Preferably, the preparation method of the flaky aluminum oxide modifier is:
[0022] S01: placing the flake aluminum oxide in a proton irradiation box for irradiation for 5 to 10 minutes, with an irradiation power of 200 to 220 W, and obtaining a flake aluminum oxide irradiation agent after the irradiation is completed;
[0023] S02: Add 5-10% of organic alcohol amine to the flaky alumina irradiating agent, and perform ball milling treatment. The ball milling speed of the ball milling treatment is 1300-1400r / min, and the ball milling time is 45-55min. After the ball milling is completed, wash with water and dry to obtain the flaky alumina modifier.
[0024] After irradiation treatment, the activity of flaky alumina is improved. Through ball milling with organic alcohol amine, the binding force with the whisker-adjusting glass microbead dual-effect agent can be improved, and the synergistic effect is improved, so that the two work in coordination and the performance of the product is further improved.
[0025] The present invention also provides a method for preparing a nanoparticle-modified aerogel material, comprising the following steps:
[0026] Step 1: Stir and mix the phenolic resin adhesive, the whisker regulating glass microbead dual-effect agent, the chitosan aqueous solution, the silane coupling agent KH560, the flaky alumina modifier, and ethanol in sequence to obtain a modified adhesive agent;
[0027] Step 2: Using the gel core layer as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, the thickness of the glue coating layer is 4 to 6 μm, and finally immersed in a nanoparticle modification liquid. After the immersion is completed, the nanoparticle modified aerogel material of the present invention is obtained by washing with water and drying.
[0028] Preferably, the immersion pressure of the immersion treatment is 10-15 MPa, and the immersion time is 20-30 min.
[0029] Preferably, the preparation method of the nanoparticle modified liquid is: preheat 5 to 10 parts of nano bentonite at 50 to 55° C. for 1 to 2 hours, then add the mixture into 20 to 25 parts of acrylic emulsion and mix well to obtain the nanoparticle modified liquid.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The nanoparticle modified aerogel material of the present invention adopts a gel core layer of silica aerogel as a material as a matrix, is infiltrated by a modified glue liquid agent, and then is immersed in a nanoparticle modified liquid. Through the coordinated and coordinated improvement of the two, the thermal insulation and wear resistance of the product can be coordinated and improved, and the acid corrosion resistance and temperature resistance stability of the product are further improved. The modified glue liquid agent adopts a phenolic resin adhesive as a matrix, and is matched with a whisker-adjusting glass microbead dual-effect agent, a chitosan aqueous solution, a silane coupling agent KH560, and a flaky aluminum oxide modifier as raw materials for mutual coordination and mutual assistance. Through the coordinated optimization of the whisker-adjusting glass microbead dual-effect agent and the flaky aluminum oxide modifier, the wear resistance and thermal insulation matrix performance of the product are significantly improved. The nanoparticle modified liquid matched with nano-bentonite is coated on the surface of the product, which can play a barrier synergistic effect, further enhance the thermal insulation, acid corrosion resistance and temperature resistance of the product, and the performance of the product is further improved through the mutual coordination and joint assistance between the raw materials. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] A nanoparticle-modified aerogel material of this embodiment, wherein the aerogel material uses a gel core layer made of silica aerogel as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, and finally is immersed in a nanoparticle modified liquid to obtain a nanoparticle-modified aerogel material;
[0034] The modified adhesive comprises the following raw materials in parts by weight:
[0035] 35-40 parts of phenolic resin adhesive, 16-22 parts of whisker regulating glass microbead dual-effect agent, 4-8 parts of chitosan aqueous solution, 3-6 parts of silane coupling agent KH560, 2-5 parts of flaky aluminum oxide modifier, and 30-40 parts of ethanol.
[0036] The mass fraction of the chitosan aqueous solution in this embodiment is 4-9%.
[0037] The preparation method of the whisker regulating glass microsphere dual-effect agent of this embodiment is:
[0038] S01: adding silicon carbide whiskers to yttrium nitrate solution at a weight ratio of 1:6, then adding sodium dodecyl sulfate solution with a weight of 5-10% of the total amount of silicon carbide whiskers and sodium silicate aqueous solution with a weight of 3-5% of the total amount of silicon carbide whiskers, stirring evenly to obtain a silicon carbide whisker conditioning solution;
[0039] S02: adding hydrochloric acid accounting for 5-10% of the total amount of the sodium alginate aqueous solution and silica sol accounting for 1-5% of the total amount of the sodium alginate aqueous solution to a sodium alginate aqueous solution having a mass fraction of 10-15%, stirring evenly to obtain a pre-modified solution;
[0040] S03: The glass microspheres are first treated at 100-110°C for 10-20 minutes, then cooled to 40-45°C at a rate of 1-3°C / min, kept warm, and then 10-15% of the total amount of the warmed product is added with a pre-modified liquid, ball milled for 1-2 hours at a ball milling speed of 1000-1500r / min, and after the ball milling is completed, washed with water and dried to obtain pre-adjusted glass microspheres;
[0041] S04: Adding the regulating glass microbeads into the silicon carbide whisker regulating liquid at a weight ratio of 1:5 for stirring and reaction treatment, and after the stirring is completed, washing and drying are performed to obtain the whisker regulating glass microbead dual-effect agent.
[0042] The mass fraction of the yttrium nitrate solution in this embodiment is 3-6%; the mass fraction of the sodium silicate aqueous solution is 10-15%.
[0043] The sodium dodecyl sulfate solution of this embodiment is prepared by a 6% by mass sodium dodecyl sulfate aqueous solution and a 2% by mass lanthanum chloride solution in a weight ratio of 3:1.
[0044] The rotation speed of the S04 stirring reaction treatment in this embodiment is 550-750 r / min, the stirring time is 20-30 min, and the stirring temperature is 45-48°C.
[0045] The preparation method of the flaky aluminum oxide modifier of this embodiment is:
[0046] S01: placing the flake aluminum oxide in a proton irradiation box for irradiation for 5 to 10 minutes, with an irradiation power of 200 to 220 W, and obtaining a flake aluminum oxide irradiation agent after the irradiation is completed;
[0047] S02: Add 5-10% of organic alcohol amine to the flaky alumina irradiating agent, and perform ball milling treatment. The ball milling speed of the ball milling treatment is 1300-1400r / min, and the ball milling time is 45-55min. After the ball milling is completed, wash with water and dry to obtain the flaky alumina modifier.
[0048] A method for preparing a nanoparticle-modified aerogel material in this embodiment comprises the following steps:
[0049] Step 1: Stir and mix the phenolic resin adhesive, the whisker regulating glass microbead dual-effect agent, the chitosan aqueous solution, the silane coupling agent KH560, the flaky alumina modifier, and ethanol in sequence to obtain a modified adhesive agent;
[0050] Step 2: Using the gel core layer as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, the thickness of the glue coating layer is 4 to 6 μm, and finally immersed in a nanoparticle modification liquid. After the immersion is completed, the nanoparticle modified aerogel material of the present invention is obtained by washing with water and drying.
[0051] The immersion pressure of the immersion treatment in this embodiment is 10-15 MPa, and the immersion time is 20-30 min.
[0052] The preparation method of the nanoparticle modified liquid of this embodiment is: 5-10 parts of nano bentonite are preheated at 50-55° C. for 1-2 hours, and then added to 20-25 parts of acrylic emulsion and mixed to obtain the nanoparticle modified liquid.
[0053] Example 1.
[0054] A nanoparticle-modified aerogel material of this embodiment, wherein the aerogel material uses a gel core layer made of silica aerogel as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, and finally is immersed in a nanoparticle modified liquid to obtain a nanoparticle-modified aerogel material;
[0055] The modified adhesive comprises the following raw materials in parts by weight:
[0056] 35 parts of phenolic resin adhesive, 16 parts of whisker regulating glass microbead dual-effect agent, 4 parts of chitosan aqueous solution, 3 parts of silane coupling agent KH560, 2 parts of flaky aluminum oxide modifier, and 30 parts of ethanol.
[0057] The mass fraction of the chitosan aqueous solution in this embodiment is 4%.
[0058] The preparation method of the whisker regulating glass microsphere dual-effect agent of this embodiment is:
[0059] S01: adding silicon carbide whiskers to yttrium nitrate solution at a weight ratio of 1:6, then adding sodium dodecyl sulfate solution with a weight ratio of 5% of the total amount of silicon carbide whiskers and sodium silicate aqueous solution with a weight ratio of 3% of the total amount of silicon carbide whiskers, stirring evenly to obtain a silicon carbide whisker conditioning solution;
[0060] S02: adding hydrochloric acid accounting for 5% of the total amount of the sodium alginate aqueous solution and silica sol accounting for 1% of the total amount of the sodium alginate aqueous solution to a sodium alginate aqueous solution having a mass fraction of 10%, stirring evenly to obtain a pre-modified solution;
[0061] S03: The glass microspheres are first treated at 100°C for 10 minutes, then cooled to 40°C at a rate of 1°C / min, kept warm, and then 10% of the total amount of the warmed product is added with a pre-modified liquid, ball milled for 1 hour, the ball milling speed is 1000r / min, and after the ball milling is completed, the pre-adjusted glass microspheres are washed with water and dried to obtain;
[0062] S04: Adding the regulating glass microbeads into the silicon carbide whisker regulating liquid at a weight ratio of 1:5 for stirring and reaction treatment, and after the stirring is completed, washing and drying are performed to obtain the whisker regulating glass microbead dual-effect agent.
[0063] The mass fraction of the yttrium nitrate solution in this embodiment is 3%; the mass fraction of the sodium silicate aqueous solution is 10%.
[0064] The sodium dodecyl sulfate solution of this embodiment is prepared by a 6% by mass sodium dodecyl sulfate aqueous solution and a 2% by mass lanthanum chloride solution in a weight ratio of 3:1.
[0065] The rotation speed of the S04 stirring reaction treatment in this embodiment is 550 r / min, the stirring time is 20 min, and the stirring temperature is 45°C.
[0066] The preparation method of the flaky aluminum oxide modifier of this embodiment is:
[0067] S01: placing the flake aluminum oxide in a proton irradiation box for 5 minutes, the irradiation power is 200W, and after the irradiation is completed, a flake aluminum oxide irradiation agent is obtained;
[0068] S02: Add 5% of organic alcohol amine to the flaky alumina irradiating agent, and perform ball milling treatment. The ball milling speed of the ball milling treatment is 1300r / min, and the ball milling time is 45min. After the ball milling is completed, wash with water and dry to obtain the flaky alumina modifier.
[0069] A method for preparing a nanoparticle-modified aerogel material in this embodiment comprises the following steps:
[0070] Step 1: Stir and mix the phenolic resin adhesive, the whisker regulating glass microbead dual-effect agent, the chitosan aqueous solution, the silane coupling agent KH560, the flaky alumina modifier, and ethanol in sequence to obtain a modified adhesive agent;
[0071] Step 2: Using the gel core layer as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, the thickness of the glue coating layer is 4 μm, and finally immersed in a nanoparticle modification liquid. After the immersion is completed, the nanoparticle-modified aerogel material of the present invention is obtained by washing with water and drying.
[0072] The immersion pressure of the immersion treatment in this embodiment is 10 MPa, and the immersion time is 20 min.
[0073] The preparation method of the nanoparticle modified liquid of this embodiment is: 5 parts of nano bentonite are preheated at 50° C. for 1 hour, and then added into 20 parts of acrylic emulsion and mixed to obtain the nanoparticle modified liquid.
[0074] Example 2.
[0075] A nanoparticle-modified aerogel material of this embodiment, wherein the aerogel material uses a gel core layer made of silica aerogel as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, and finally is immersed in a nanoparticle modified liquid to obtain a nanoparticle-modified aerogel material;
[0076] The modified adhesive comprises the following raw materials in parts by weight:
[0077] 40 parts of phenolic resin adhesive, 22 parts of whisker regulating glass microbead dual-effect agent, 8 parts of chitosan aqueous solution, 6 parts of silane coupling agent KH560, 5 parts of flaky aluminum oxide modifier, and 40 parts of ethanol.
[0078] The mass fraction of the chitosan aqueous solution in this embodiment is 9%.
[0079] The preparation method of the whisker regulating glass microsphere dual-effect agent of this embodiment is:
[0080] S01: adding silicon carbide whiskers to yttrium nitrate solution at a weight ratio of 1:6, then adding sodium dodecyl sulfate solution with a weight ratio of 10% of the total amount of silicon carbide whiskers and sodium silicate aqueous solution with a weight ratio of 5% of the total amount of silicon carbide whiskers, stirring evenly to obtain a silicon carbide whisker conditioning solution;
[0081] S02: adding hydrochloric acid accounting for 10% of the total amount of the sodium alginate aqueous solution and silica sol accounting for 5% of the total amount of the sodium alginate aqueous solution to a sodium alginate aqueous solution having a mass fraction of 15%, stirring evenly to obtain a pre-modified solution;
[0082] S03: The glass microspheres are first treated at 110°C for 20 minutes, then cooled to 45°C at a rate of 3°C / min, kept warm, and then 15% of the total amount of the warmed product is added with a pre-modified liquid, ball milled for 2 hours at a ball milling speed of 1500r / min, and after the ball milling is completed, washed with water and dried to obtain pre-adjusted glass microspheres;
[0083] S04: Adding the regulating glass microbeads into the silicon carbide whisker regulating liquid at a weight ratio of 1:5 for stirring and reaction treatment, and after the stirring is completed, washing and drying are performed to obtain the whisker regulating glass microbead dual-effect agent.
[0084] The mass fraction of the yttrium nitrate solution in this embodiment is 6%; the mass fraction of the sodium silicate aqueous solution is 15%.
[0085] The sodium dodecyl sulfate solution of this embodiment is prepared by a 6% by mass sodium dodecyl sulfate aqueous solution and a 2% by mass lanthanum chloride solution in a weight ratio of 3:1.
[0086] The rotation speed of the S04 stirring reaction treatment in this embodiment is 750 r / min, the stirring time is 30 min, and the stirring temperature is 48°C.
[0087] The preparation method of the flaky aluminum oxide modifier of this embodiment is:
[0088] S01: placing the flake aluminum oxide in a proton irradiation box and irradiating for 10 minutes at an irradiation power of 220W, and obtaining a flake aluminum oxide irradiation agent after the irradiation is completed;
[0089] S02: Add 10% of the total amount of organic alcohol amine to the flaky alumina irradiating agent, and perform ball milling treatment. The ball milling speed of the ball milling treatment is 1400r / min, and the ball milling time is 55min. After the ball milling is completed, wash with water and dry to obtain the flaky alumina modifier.
[0090] A method for preparing a nanoparticle-modified aerogel material in this embodiment comprises the following steps:
[0091] Step 1: Stir and mix the phenolic resin adhesive, the whisker regulating glass microbead dual-effect agent, the chitosan aqueous solution, the silane coupling agent KH560, the flaky alumina modifier, and ethanol in sequence to obtain a modified adhesive agent;
[0092] Step 2: The gel core layer is used as a matrix, and the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, the thickness of the glue coating layer is 6um, and finally immersed in a nanoparticle modification liquid. After the immersion is completed, the nanoparticle modified aerogel material of the present invention is obtained by washing with water and drying.
[0093] The immersion pressure of the immersion treatment in this embodiment is 15 MPa, and the immersion time is 30 min.
[0094] The preparation method of the nanoparticle modified liquid of this embodiment is: 10 parts of nano bentonite are preheated at 55° C. for 2 hours, and then added into 25 parts of acrylic emulsion and mixed to obtain the nanoparticle modified liquid.
[0095] Example 3.
[0096] A nanoparticle-modified aerogel material of this embodiment, wherein the aerogel material uses a gel core layer made of silica aerogel as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, and finally is immersed in a nanoparticle modified liquid to obtain a nanoparticle-modified aerogel material;
[0097] The modified adhesive comprises the following raw materials in parts by weight:
[0098] 37.5 parts of phenolic resin adhesive, 20 parts of whisker regulating glass microbead dual-effect agent, 6 parts of chitosan aqueous solution, 4.5 parts of silane coupling agent KH560, 3.5 parts of flaky aluminum oxide modifier, and 35 parts of ethanol.
[0099] The mass fraction of the chitosan aqueous solution in this embodiment is 6.5%.
[0100] The preparation method of the whisker regulating glass microsphere dual-effect agent of this embodiment is:
[0101] S01: adding silicon carbide whiskers to yttrium nitrate solution at a weight ratio of 1:6, then adding sodium dodecyl sulfate solution with a total amount of 7.5% of the silicon carbide whiskers and sodium silicate aqueous solution with a total amount of 4% of the silicon carbide whiskers, stirring evenly to obtain a silicon carbide whisker conditioning solution;
[0102] S02: adding hydrochloric acid accounting for 7.5% of the total amount of the sodium alginate aqueous solution and silica sol accounting for 3% of the total amount of the sodium alginate aqueous solution to a sodium alginate aqueous solution having a mass fraction of 12.5%, stirring evenly to obtain a pre-modified solution;
[0103] S03: The glass microspheres are first treated at 105°C for 15 minutes, then cooled to 42.5°C at a rate of 2°C / min, kept warm, and then 12.5% of the total amount of the warmed product is added with a pre-modified liquid, ball milled for 1.5 hours at a ball milling speed of 1250r / min, and after the ball milling is completed, washed with water and dried to obtain pre-adjusted glass microspheres;
[0104] S04: Adding the regulating glass microbeads into the silicon carbide whisker regulating liquid at a weight ratio of 1:5 for stirring and reaction treatment, and after the stirring is completed, washing and drying are performed to obtain the whisker regulating glass microbead dual-effect agent.
[0105] The mass fraction of the yttrium nitrate solution in this embodiment is 4.5%; the mass fraction of the sodium silicate aqueous solution is 12.5%.
[0106] The sodium dodecyl sulfate solution of this embodiment is prepared by a 6% by mass sodium dodecyl sulfate aqueous solution and a 2% by mass lanthanum chloride solution in a weight ratio of 3:1.
[0107] The rotation speed of the S04 stirring reaction treatment in this embodiment is 600 r / min, the stirring time is 25 min, and the stirring temperature is 46°C.
[0108] The preparation method of the flaky aluminum oxide modifier of this embodiment is:
[0109] S01: placing the flake aluminum oxide in a proton irradiation box and irradiating for 7.5 minutes at an irradiation power of 210W, and obtaining a flake aluminum oxide irradiation agent after the irradiation is completed;
[0110] S02: Add 7.5% of organic alcohol amine to the flaky alumina irradiating agent, and perform ball milling. The ball milling speed is 1350r / min, and the ball milling time is 50min. After the ball milling is completed, wash with water and dry to obtain the flaky alumina modifier.
[0111] A method for preparing a nanoparticle-modified aerogel material in this embodiment comprises the following steps:
[0112] Step 1: Stir and mix the phenolic resin adhesive, the whisker regulating glass microbead dual-effect agent, the chitosan aqueous solution, the silane coupling agent KH560, the flaky alumina modifier, and ethanol in sequence to obtain a modified adhesive agent;
[0113] Step 2: The gel core layer is used as a matrix, and the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, the thickness of the glue coating layer is 5um, and finally immersed in a nanoparticle modification liquid. After the immersion is completed, the nanoparticle modified aerogel material of the present invention is obtained by washing with water and drying.
[0114] The immersion pressure of the immersion treatment in this embodiment is 12.5 MPa, and the immersion time is 25 min.
[0115] The preparation method of the nanoparticle modified liquid of this embodiment is as follows: 7.5 parts of nano bentonite are preheated at 52° C. for 1.5 hours, and then added into 22.5 parts of acrylic emulsion and mixed to obtain the nanoparticle modified liquid.
[0116] Example 4.
[0117] A nanoparticle-modified aerogel material of this embodiment, wherein the aerogel material uses a gel core layer made of silica aerogel as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, and finally is immersed in a nanoparticle modified liquid to obtain a nanoparticle-modified aerogel material;
[0118] The modified adhesive comprises the following raw materials in parts by weight:
[0119] 36 parts of phenolic resin adhesive, 18 parts of whisker regulating glass microbead dual-effect agent, 5 parts of chitosan aqueous solution, 4 parts of silane coupling agent KH560, 3 parts of flaky aluminum oxide modifier, and 32 parts of ethanol.
[0120] The mass fraction of the chitosan aqueous solution in this embodiment is 5%.
[0121] The preparation method of the whisker regulating glass microsphere dual-effect agent of this embodiment is:
[0122] S01: adding silicon carbide whiskers to yttrium nitrate solution at a weight ratio of 1:6, then adding sodium dodecyl sulfate solution with a weight ratio of 6% of the total amount of silicon carbide whiskers and sodium silicate aqueous solution with a weight ratio of 4% of the total amount of silicon carbide whiskers, stirring evenly to obtain a silicon carbide whisker conditioning solution;
[0123] S02: adding hydrochloric acid accounting for 6% of the total amount of the sodium alginate aqueous solution and silica sol accounting for 2% of the total amount of the sodium alginate aqueous solution to a sodium alginate aqueous solution having a mass fraction of 12%, stirring evenly to obtain a pre-modified solution;
[0124] S03: The glass microspheres were first treated at 102°C for 12 minutes, then cooled to 42°C at a rate of 1.2°C / min, kept warm, and then 12% of the total amount of the warmed product was added with a pre-modified liquid, ball milled for 1.2 hours at a ball milling speed of 1250r / min, and after the ball milling was completed, washed with water and dried to obtain pre-adjusted glass microspheres;
[0125] S04: Adding the regulating glass microbeads into the silicon carbide whisker regulating liquid at a weight ratio of 1:5 for stirring and reaction treatment, and after the stirring is completed, washing and drying are performed to obtain the whisker regulating glass microbead dual-effect agent.
[0126] The mass fraction of the yttrium nitrate solution in this embodiment is 4%; the mass fraction of the sodium silicate aqueous solution is 12%.
[0127] The sodium dodecyl sulfate solution of this embodiment is prepared by a 6% by mass sodium dodecyl sulfate aqueous solution and a 2% by mass lanthanum chloride solution in a weight ratio of 3:1.
[0128] The rotation speed of the S04 stirring reaction treatment in this embodiment is 580 r / min, the stirring time is 22 min, and the stirring temperature is 46°C.
[0129] The preparation method of the flaky aluminum oxide modifier of this embodiment is:
[0130] S01: placing the flaky aluminum oxide in a proton irradiation box and irradiating for 6 minutes at an irradiation power of 205W, and obtaining a flaky aluminum oxide irradiation agent after the irradiation is completed;
[0131] S02: Add 6% of organic alcohol amine to the flaky alumina irradiating agent, and perform ball milling. The ball milling speed is 1320r / min, and the ball milling time is 48min. After the ball milling is completed, wash with water and dry to obtain the flaky alumina modifier.
[0132] A method for preparing a nanoparticle-modified aerogel material in this embodiment comprises the following steps:
[0133] Step 1: Stir and mix the phenolic resin adhesive, the whisker regulating glass microbead dual-effect agent, the chitosan aqueous solution, the silane coupling agent KH560, the flaky alumina modifier, and ethanol in sequence to obtain a modified adhesive agent;
[0134] Step 2: The gel core layer is used as a matrix, and the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, the thickness of the glue coating layer is 5um, and finally immersed in a nanoparticle modification liquid. After the immersion is completed, the nanoparticle modified aerogel material of the present invention is obtained by washing with water and drying.
[0135] The immersion pressure of the immersion treatment in this embodiment is 12 MPa, and the immersion time is 22 min.
[0136] The preparation method of the nanoparticle modified liquid of this embodiment is as follows: 6 parts of nano-bentonite are preheated at 52° C. for 1.2 hours, and then added into 22 parts of acrylic emulsion and mixed to obtain the nanoparticle modified liquid.
[0137] Comparative Example 1.
[0138] The difference from Example 3 is that the whisker regulating glass microbead dual-effect agent is not added to the modified adhesive.
[0139] Comparative Example 2.
[0140] The difference from Example 3 is that the pre-adjusted glass microspheres are replaced by glass microspheres in the preparation of the whisker-adjusting glass microsphere dual-effect agent in the modified adhesive.
[0141] Comparative Example 3.
[0142] The difference from Example 3 is that no pre-modified liquid is used in the preparation of the whisker-adjusting glass microbead dual-effect agent in the modified adhesive, and direct ball milling treatment is performed.
[0143] Comparative Example 4.
[0144] The difference from Example 3 is that no sodium dodecyl sulfate solution is added to the silicon carbide whisker regulating solution in the preparation of the whisker regulating glass microbead dual-effect agent in the modified adhesive.
[0145] Comparative Example 5.
[0146] The difference from Example 3 is that no flaky aluminum oxide modifier is added.
[0147] Comparative Example 6.
[0148] The difference from Example 3 is that organic alcohol amine is not used in the preparation of the flaky aluminum oxide modifier, and the flaky aluminum oxide modifier is directly ball-milled.
[0149] Comparative Example 7.
[0150] The difference from Example 3 is that the nanoparticle modification liquid immersion treatment is not used.
[0151] The products of Examples 1 to 4 and Comparative Examples 1 to 7 were tested for wear resistance and thermal conductivity. At the same time, the products were placed in 2% hydrochloric acid for 2 hours and then placed at 65°C for 5 hours to test the acid corrosion resistance and temperature stability. The test results are as follows
[0152]
[0153] It can be seen from Comparative Examples 1-7 and Examples 1-4 that;
[0154] The product of Example 3 has excellent wear resistance and excellent thermal insulation performance, and the two can be improved in a coordinated manner. In addition, the product has excellent stability in corrosion resistance and temperature resistance;
[0155] As can be seen from Comparative Examples 1-7 and Example 3, the present invention does not add a whisker-adjusting glass microbead dual-effect agent, does not add a flaky alumina modifier, and does not use a nanoparticle modified liquid for immersion treatment, and the performance of the product deteriorates significantly. The three are deployed to synergize and enhance the performance, and the performance effect of the product is the most obvious. At the same time, the pre-adjusted glass microbeads are replaced by glass microbeads in the preparation of the whisker-adjusting glass microbead dual-effect agent in the modified glue agent, and the pre-modified liquid is not used in the preparation of the whisker-adjusting glass microbead dual-effect agent in the modified glue agent, and the direct ball milling treatment is performed. In the preparation of the whisker-adjusting glass microbead dual-effect agent in the modified glue agent, sodium lauryl sulfate liquid is not added to the silicon carbide whisker regulating liquid, and organic alcohol amines are not used in the preparation of the flaky alumina modifier, and the direct ball milling treatment is performed. The performance of the product has a tendency to deteriorate. Only the whisker-adjusting glass microbead dual-effect agent prepared by the method of the present invention has the most significant performance effect of the product.
[0156] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0157] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A nanoparticle-modified aerogel material, characterized in that: The aerogel material uses a gel core layer made of silica aerogel as a matrix, the gel core layer is infiltrated into a modified glue liquid to form a glue coating layer, and finally is immersed in a nanoparticle modified liquid to obtain a nanoparticle modified aerogel material; The modified adhesive comprises the following raw materials in parts by weight: 35-40 parts of phenolic resin adhesive, 16-22 parts of whisker regulating glass microbead dual-effect agent, 4-8 parts of chitosan aqueous solution, 3-6 parts of silane coupling agent KH560, 2-5 parts of flaky aluminum oxide modifier, and 30-40 parts of ethanol; The mass fraction of the chitosan aqueous solution is 4 to 9%; The preparation method of the whisker regulating glass microbead dual-effect agent is as follows: S01: adding silicon carbide whiskers to yttrium nitrate solution at a weight ratio of 1:6, then adding sodium dodecyl sulfate solution with a weight of 5-10% of the total amount of silicon carbide whiskers and sodium silicate aqueous solution with a weight of 3-5% of the total amount of silicon carbide whiskers, stirring evenly to obtain a silicon carbide whisker conditioning solution; S02: adding hydrochloric acid accounting for 5-10% of the total amount of the sodium alginate aqueous solution and silica sol accounting for 1-5% of the total amount of the sodium alginate aqueous solution to a sodium alginate aqueous solution having a mass fraction of 10-15%, stirring evenly to obtain a pre-modified solution; S03: The glass microspheres are first treated at 100-110°C for 10-20 minutes, then cooled to 40-45°C at a rate of 1-3°C / min, kept warm, and then 10-15% of the total amount of the warmed product is added with a pre-modified liquid, ball milled for 1-2 hours at a ball milling speed of 1000-1500r / min, and after the ball milling is completed, washed with water and dried to obtain pre-adjusted glass microspheres; S04: adding the regulating glass microbeads into the silicon carbide whisker regulating liquid at a weight ratio of 1:5 for stirring and reacting, washing with water and drying after the stirring is completed to obtain the whisker regulating glass microbead dual-effect agent; The mass fraction of the yttrium nitrate solution is 3-6%; the mass fraction of the sodium silicate aqueous solution is 10-15%; The sodium dodecyl sulfate solution is prepared by mixing a 6% sodium dodecyl sulfate aqueous solution and a 2% lanthanum chloride solution in a weight ratio of 3:
1. The speed of the S04 stirring reaction treatment is 550-750 r / min, the stirring time is 20-30 min, and the stirring temperature is 45-48°C; The preparation method of the flaky aluminum oxide modifier is as follows: a01: placing the flake aluminum oxide in a proton irradiation box and irradiating it for 5 to 10 minutes at an irradiation power of 200 to 220 W, and obtaining a flake aluminum oxide irradiation agent after the irradiation is completed; a02: Add 5-10% of organic alcohol amine to the flaky alumina irradiating agent, and perform ball milling treatment. The ball milling speed is 1300-1400r / min, and the ball milling time is 45-55min. After the ball milling is completed, wash with water and dry to obtain the flaky alumina modifier.
2. A method for preparing the nanoparticle-modified aerogel material as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Stir and mix the phenolic resin adhesive, the whisker regulating glass microbead dual-effect agent, the chitosan aqueous solution, the silane coupling agent KH560, the flaky alumina modifier, and ethanol in sequence to obtain a modified adhesive agent; Step 2: The gel core layer is used as a matrix, and the gel core layer is infiltrated into the modified glue liquid to form a glue coating layer. The thickness of the glue coating layer is 4 to 6 um, and finally immersed in the nanoparticle modification liquid. After the immersion is completed, it is washed with water and dried to obtain a nanoparticle modified aerogel material.
3. The method for preparing a nanoparticle-modified aerogel material according to claim 2, characterized in that: The immersion pressure of the immersion treatment is 10-15 MPa, and the immersion time is 20-30 minutes.
4. The method for preparing a nanoparticle-modified aerogel material according to claim 3, characterized in that: The preparation method of the nanoparticle modified liquid is as follows: 5 to 10 parts of nano bentonite are preheated at 50 to 55° C. for 1 to 2 hours, and then added into 20 to 25 parts of acrylic emulsion and mixed to obtain the nanoparticle modified liquid.
